Guidelines for the Development of Silp-Isan Klong Yao Band Performance Style - Rukbancha Phimprajun; Thanaporn Pengsri; Sarawut Choatchamrat; Sayam Chuangprakhon (Journal of Educational Issues, 2024)
This research aims to 1) study the style and development of the Silp-Isan Klong Yao drum band; and 2) present the guidelines to developing and creating the Klong Yao performance style, which is an integration to teach the Klong Yao ensemble course including of students majoring in folk music, College of Music, Mahasarakham University. The researchers studied preliminary studies based on research and collect academic papers, textbooks, and reports. In addition, the researchers conducted studies based on field data collection from knowledge groups, practitioners, and individual groups. The results showed that. 1) The style and development of the Silp-Isan Klong Yao Band in terms of the form consists of musical instruments used in the Silp-Isan Klong Yao bands, long drum calibration how to play the desired sound, putting a bran drummer on tambourine, a ceremony to pay respects to teachers, dressing, and Isan long drumming patterns and techniques; 2) Guidelines for developing and creating a Klong Yao band performance style can be divided into two styles: 1) Long drum band performance style: ancient drum beats before the Isan long drum show use the band’s opening song with the New Sutsanan melody and Lai Mak Gab Gab Lam Plearn melody. The tempo of 2/4 is mixed with the tempo of 4/4 and followed by an ancient drum rhythm based on the rhythm of a creative Isan long drum; 2) Klong Yao band performance style applied rhythm consists of Soy Tang Ubon pattern, Tang-Wai-Aok-Sing pattern, Sutsanan pattern is mixed with Tong-Wai pattern, and Lam-sing keyboard with using the structure of Lam Plearn pattern. The bass keyboard uses the Cm scale and uses popular classical songs to the rhythm to be consistent with the row deployment and concatenation show. In summary, Sin-Isan drum band performance has developed styles continuously.